Advances in Structure-Based PARP1 Inhibitors: Implications for Cancer Treatment - Balachandran, Hardha; Das, Sinjini; Byran, Gowramma; Murugesan, Senthilkumar; Karri, Sathya Narayana Reddy; Rajagopal, Kalirajan (Current Enzyme Inhibition, 2025)
Cancer is characterized by the uncontrolled proliferation of abnormal cells that escape the body's standard regulatory mechanisms. Under normal conditions, cells grow, divide, and die in an orderly manner, but cancerous cells lose this control, growing uncontrollably and invading surrounding tissues. Poly(ADP-ribose) polymerase 1 (PARP1) is a crucial enzyme in this DNA repair process, helping to fix single-strand breaks. PARP inhibitors (PARPi) are a class of drugs that target and block the activity of the PARP1 enzyme, impairing its ability to repair DNA damage. By inhibiting PARP1, these drugs lead to an accumulation of DNA damage in cancer cells, which eventually becomes overwhelming and leads to cell death. This mechanism is particularly effective in cancers with deficiencies in other DNA repair pathways, such as those with BRCA1 and BRCA2 gene mutations. Several PARPi, including Olaparib, Niraparib, and Rucaparib, have been approved by the U.S. Food and Drug Administration (FDA) for use in treating cancers like breast, ovarian, and prostate cancer, particularly in patients with BRCA mutations. The evolution and development of PARP inhibitors have focused on modifying their chemical structure to increase their effectiveness. The design of PARPi also aims to improve their bioavailability, ensuring that the drugs are effectively absorbed into the body and can reach the tumor site in sufficient concentrations. Further developments may also involve combining PARPi with other treatments, such as chemotherapy or immunotherapy, to enhance their overall efficacy.
Keywords: targeted therapy